2009 International Association of Computer Science and Information Technology - Spring Conference 2009
DOI: 10.1109/iacsit-sc.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Proteins

Abstract: There is lot of work gone into proteins to understand the nature of proteins. Hydrophobic interaction is the dominant force that drives the proteins to carry out the biochemical reactions in all living being. Carbon is the only element that contributes towards this hydrophobic interaction. In this study the carbon distribution along the protein sequence has been computed by representing the protein sequence as a series of atoms instead of amino acids. Given any length, there is a maximum frequency occurs at 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The carbon distribution along the sequence was analysed using CARBANA program available online [3]. A outer length of 700 atoms are chosen here to have broader view on carbon distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon distribution along the sequence was analysed using CARBANA program available online [3]. A outer length of 700 atoms are chosen here to have broader view on carbon distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Recently it is reported that globular proteins prefer to have 31.45% of carbon for its stability and can be used as standard for carbon distribution analysis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins evolve based on carbon content and may influence the code in genes. It is reported that proteins prefers to have 31.45% of carbon for its stability [2], [3]. Depending upon the carbon content, the protein and the corresponding mRNA survive and passed to next generation.…”
Section: Resultsmentioning
confidence: 99%
“…Our idea of conversion of arrangement of carbon profile may be of useful from nearing the untold answer to the human sufferings. Our idea was to go back a decade of carbon analysis finding maintenance of carbon value within the system of biologically important protein molecule which was analyzed after careful observation that protein attempting to maintain fraction of carbon 0.3144 at all level [1]. Arrangements are in such a way that aminoacid composition arranged according to the need based of carbon profile of law of rule.…”
Section: Introductionmentioning
confidence: 99%